Prevalence of Hypertension and Obesity: Profile of Mitochondrial Function and Markers of Inflammation and Oxidative Stress - García-Sánchez, Andrés; Gómez-Hermosillo, Luis; Casillas-Moreno, Jorge; Pacheco-Moisés, Fermín; Campos-Bayardo, Tannia Isabel; Román-Rojas, Daniel; Miranda-Díaz, Alejandra Guillermina (Antioxidants, 2023)
Obesity and hypertension are health problems of increasing prevalence in developed countries. The link between obesity and hypertension is not yet fully determined. Oxidative stress (OS) and mitochondrial function may play a role in obesity-associated hypertension. A cross-sectional study with 175 subjects with normal weight, overweight, or obese who attended a medical check-up was included. The subjects were divided according to the body mass index (BMI) into normal-weight (n-53), overweight (n-84), and obesity (n-38). Hypertension was also evaluated. To measure mitochondrial function, ATP hydrolysis and ATP synthesis in platelets and serum, respectively, were determined. Superoxide dismutase (SOD), catalase, lipohydroperoxides, 8-isoprostanes, carbonyl groups in proteins, nitric oxide (NO) metabolites, 8-hydroxy-2′-deoxyguanosine (8-OHG), 8-oxoguanine glycosylase (hOGG1), tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) were measured by standard colorimetric or immunoassay methods. Obese subjects showed lower ATP hydrolysis activity than normal weight and overweight subjects (p < 0.01). No differences between those groups were found in ATP synthase and catalase activities, lipid hydroperoxides, carbonyl groups in proteins, 8-isoprostanes, and NO metabolites. In the obesity group, SOD activity (p < 0.01) was decreased while 8-OHG (p < 0.01) was increased. Subjects with hypertension showed increased 8-OHG (p < 0.01) and less reparative enzyme (hOGG1 p = 0.04) than subjects with normal weight. Moreover, we found a decrease of SOD (p < 0.01), catalase activities (p = 0.04), NO metabolites (p < 0.01), and increases of carbonyl groups in proteins (p = 0.01), TNF-α (p < 0.01) and IL-6 (p < 0.01 in hypertensive subjects. Obese subjects show a decrease in ATP hydrolysis. The decrease in ATP hydrolysis rate and ATP synthesis and an increase in OS and inflammation markers were associated with the hypertensive state.